The Phenomenon of Juvenile Delinquent Behavior (Case Study of Teenagers in Labunia Village) - Prendi Pradana; Batmang; Moh. Safrudin (Dirasah: Jurnal Pendidikan Islam, 2025)
The basis of this research aims to describe the phenomenon of juvenile delinquent behavior in Labunia Village, to determine the occurrence of juvenile delinquent behavior in Labunia Village, and to overcome juvenile delinquent behavior that occurs in Labunia Village. Based on the research title that was raised, namely “The Phenomenon of Juvenile Delinquent Behavior (Case Study of Juvenile Delinquency in Labunia Village, Wakorumba Selatan Subdistrict)”, the research method used is qualitative research with a type of case study research, to examine an event or case that occurs by looking at the relationship of all variables in the event. Labunia Village teenagers who are involved in delinquency in the form of alcohol, reckless driving and brawls. One of the main factors influencing juvenile delinquency in Labunia Village is the lack of supervision and attention from parents. Peer influence is one of the main factors causing juvenile delinquency in Labunia Village. Labunia Village teenagers tend to be influenced by their peers who have negative behaviors, such as alcohol, recklessness and fighting.Keywords: Juvenile delinquent behavior